Teodoro, A. (2020). Contesting the Global Development of Sustainable and Inclusive Education. Education Reform and the Challenges of Neoliberal Globalization. (Revista Lusófona de Educação, 2021)
Recensão crítica da obra deTeodoro, A. (2020). Contesting the Global Development of Sustainable and Inclusive Education. Education Reform and the Challenges of Neoliberal Globalization. New York and London: Routledge.